Comparative Protein Structure Modeling Using MODELLER. Issue 1 (8th September 2014) - Webb, Benjamin; Sali, Andrej
Abstract: Functional characterization of a protein sequence is one of the most frequent problems in biology. This task is usually facilitated by accurate three‐dimensional (3‐D) structure of the studied protein. In the absence of an experimentally determined structure, comparative or homology modeling can sometimes provide a useful 3‐D model for a protein that is related to at least one known protein structure. Comparative modeling predicts the 3‐D structure of a given protein sequence (target) based primarily on its alignment to one or more proteins of known structure (templates). The prediction process consists of fold assignment, target‐template alignment, model building, and model evaluation. This unit describes how to calculate comparative models using the program MODELLER and discusses all four steps of comparative modeling, frequently observed errors, and some applications. Modeling lactate dehydrogenase from Trichomonas vaginalis (TvLDH) is described as an example. The download and installation of the MODELLER software is also described. Curr. Protoc. Bioinform . 47:5.6.1‐5.6.32. © 2014 by John Wiley & Sons, Inc.